Pengaruh Persepsi Profesi Guru Pengenalan Lapangan Persekolahan Dan Efikasi Diri Terhadap Minat Menjadi Guru - Damanik, Arnold Setia; Afriza, Edi Fitriana; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Teaching is a very noble job and requires various competencies so that the teacher's work can be done optimally. The choice of the teaching profession is influenced by various factors, one of which is interest. This study aims to identify the influence of Siliwangi University FETT students' perceptions of the teaching profession, PLP experience, and their level of self-confidence (self-efficacy) on their interest in becoming teachers both partially and simultaneously. Through a quantitative approach, the population of this study amounted to 1076 FETT students of Siliwangi University class of 2020. The sampling technique used was simple random sampling of 291 students, the data collection technique used a questionnaire. The results showed that: 1) The partial test results state that the significant value is 0.160, meaning that there is no influence between the perception of the teaching profession and the interest in becoming a teacher, 2) the significance value of the introduction of the school field is 0.001, which means that there is an influence of the introduction of the school field on interest in becoming a teacher, 3) the significance value of self-efficacy is 0.000, meaning that there is an influence between self-efficacy and interest in becoming a teacher, 4) Simultaneously the significance value obtained is 0.000, meaning that there is an influence between the perception of the teaching profession, the introduction of the school field and self-efficacy on interest in becoming a teacher.